Outfoxed by RBFOX1‐A caution about ascertainment bias. Issue 6 (24th March 2014) - Kamien, Benjamin; Lionel, Anath C.; Bain, Nicole; Scherer, Stephen W.; Hunter, Matthew
<x xml:space="preserve">Abstract</x> We report on two patients with intragenic deletions of RBFOX1 and one patient with an intragenic duplication of RBFOX1. These patients, by report, all had autism spectrum disorder and/or developmental delay and had strong family histories of these conditions. We initially hypothesized that RBFOX1 was another susceptibility locus for autism spectrum disorder or developmental delay. However, epidemiological evidence examining large numbers of individuals did not support this hypothesis and the data presented here suggests that RBFOX1 intragenic copy number variants are not pathogenic. This contradicts previous reports that examined smaller numbers of patients and controls. © 2014 Wiley Periodicals, Inc.